Hyperpatulones A–F, polycyclic polyprenylated acylphloroglucinols from Hypericum patulum and their cytotoxic activities. Issue 14 (12th March 2019) - Wu, Zhong-Nan; Niu, Qian-Wen; Zhang, Yu-Bo; Luo, Ding; Li, Qing-Guo; Li, Ying-Ying; Kuang, Guang-Kai; He, Li-Jun; Wang, Guo-Cai; Li, Yao-Lan
Abstract : Six new PPAPs (1–6 ) were isolated from Hypericum patulum and compound5 exhibited significant cytotoxicities on various tumor cell lines. Abstract : Six new compounds, hyperpatulones A–F (1–6 ), along with ten additional known related derivatives (7–16 ), were isolated from Hypericum patulum (Guttiferae). Their structures were elucidated by extensive analysis of spectroscopic data (IR, UV, HRESIMS, 1D and 2D NMR), X-ray crystallography, electronic circular dichroism (ECD) spectroscopy and Rh2 (OCOCF3 )4 -induced ECD. All compounds were tested for their cytotoxic activities on human HepG-2, HeLa, MCF-7, and A549 cell lines via 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Compound5 exhibited significant cytotoxicities against HepG-2, HeLa and A549 cell lines with IC50 values of 9.52 ± 0.27, 11.87 ± 0.22 and 12.63 ± 0.12 μM, respectively.